2021
DOI: 10.1371/journal.pone.0260457
|View full text |Cite
|
Sign up to set email alerts
|

Promoting social distancing in a pandemic: Beyond good intentions

Abstract: Do reminders to promote social distancing achieve the desired effects on behavior? Much of the existing literature analyses impacts on people’s intentions to comply. We run a randomised controlled trial in Denmark to test different versions of a reminder to stay home at the beginning of the crisis. Using a two-stage design, we follow up with recipients and analyse their subsequent self-reported behaviour. We find that the reminder increases ex-ante intentions to comply when it emphasises the consequences of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
1
9
1
1
Order By: Relevance
“…One study similar to ours, carried out in Japan, tested interventions online, finding that only one treatment was significant and positive in effect (Sasaki et al, 2020). Another study found behaviorally-informed text messages to be effective in São Paulo (Boruchowicz et al, 2020), while a Danish study found that prompts were effective in changing intentions but not actions, as in our study, though this study did not use behaviorally-informed messages (Falco & Zaccagni, 2020). Many studies carried out by government teams and consultancies, such as the Behavioural Insights Team (https://www.bi.team/our-work/covid-19/), only report headline results, with full study designs not available.…”
Section: Literature Reviewcontrasting
confidence: 50%
“…One study similar to ours, carried out in Japan, tested interventions online, finding that only one treatment was significant and positive in effect (Sasaki et al, 2020). Another study found behaviorally-informed text messages to be effective in São Paulo (Boruchowicz et al, 2020), while a Danish study found that prompts were effective in changing intentions but not actions, as in our study, though this study did not use behaviorally-informed messages (Falco & Zaccagni, 2020). Many studies carried out by government teams and consultancies, such as the Behavioural Insights Team (https://www.bi.team/our-work/covid-19/), only report headline results, with full study designs not available.…”
Section: Literature Reviewcontrasting
confidence: 50%
“…While the exact wording of our outcome measures and the survey questions that underpin them, were not taken directly from other studies, they are similar to measures used in the literature. For example, our recent compliance measures are similar to those used in Bahety et al [ 29 ], Banerjee et al [ 27 ], Boruchowicz et al [ 28 ], Falco and Zaccagni [ 38 ], Hume et al [ 39 ], and Saski et al [ 33 ]; our intended compliance outcome measures are similar to those used in Carfora and Catelani [ 30 ], Favero and Pedersen [ 35 ], Hacquin et al [ 36 ], Hume et al [ 39 ], Jordan et al [ 31 ], Lunn et al [ 32 ], Sasaki et al [ 33 ], and Utych and Fowler [ 34 ]; and our concern measures are similar to those used in Banerjee et al [ 27 ] and Favero and Pedersen [ 35 ].…”
Section: Experimental Designmentioning
confidence: 97%
“…On the other hand, however, Barari et al [ 14 ], Favero and Pedersen [ 35 ], Hacquin et al [ 36 ] and Sanders et al [ 37 ], are not able to discern an effect of nudges on attitudes and beliefs about and/or intended compliance with NPIs in Italy, the United States, France, and the United Kingdom respectively. Finally, working in Denmark and the United Kingdom, Falco and Zaccagni [ 38 ] and Hume et al [ 39 ] also are unable to discern effects on recent compliance but do find positive effects on intended future compliance.…”
Section: Introductionmentioning
confidence: 99%
“…2020). Ancak birçok ülkenin COVID-19'un yayılmasını önlemek için sosyal mesafenin önemini vurguladığı sırada; bu salgına ilişkin risk algılarının Beklenti Teorisinin tam tersi yönde şekillenmesi gerektiği anlaşılmaktadır (British Broadcasting Corporatıon News, 2020;New Zealand Police, 2020;Falco ve Zaccagni, 2020;Lunn, vd. ve 2020;Utych ve Fowler, 2020).…”
Section: Covid-19'un Turizm Sektörüne Etkisiunclassified